The remarried empress. 5 - Alphatart (Novelist); HereLee (Mangaka) (Ize Press, 2023)
"Things are coming to a head between the empress, the emperor, and his mistress. Rashta's secret has been found out, Navier must scramble to save her brother from banishment, and with all the pieces in place, Sovieshu finally readies his opening gambit. The plan? File to divorce Navier! But Heinrey is making moves to capture his queen, and if Sovieshu isn't careful, he might just end up in checkmate."--Page 4 of cover.